New directions in clinical trials for frontotemporal lobar degeneration: Methods and outcome measures. Issue 1 (6th January 2020) - Boxer, Adam L.; Gold, Michael; Feldman, Howard; Boeve, Bradley F.; Dickinson, Susan L.-J.; Fillit, Howard; Ho, Carole; Paul, Robert; Pearlman, Rodney; Sutherland, Margaret; Verma, Ajay; Arneric, Stephen P.; et al.
Abstract: Introduction: Frontotemporal lobar degeneration (FTLD) is the most common form of dementia for those under 60 years of age. Increasing numbers of therapeutics targeting FTLD syndromes are being developed. Methods: In March 2018, the Association for Frontotemporal Degeneration convened the Frontotemporal Degeneration Study Group meeting in Washington, DC, to discuss advances in the clinical science of FTLD. Results: Challenges exist for conducting clinical trials in FTLD. Two of the greatest challenges are (1) the heterogeneity of FTLD syndromes leading to difficulties in efficiently measuring treatment effects and (2) the rarity of FTLD disorders leading to recruitment challenges. Discussion: New personalized endpoints that are clinically meaningful to individuals and their families should be developed. Personalized approaches to analyzing MRI data, development of new fluid biomarkers and wearable technologies will help to improve the power to detect treatment effects in FTLD clinical trials and enable new, clinical trial designs, possibly leveraged from the experience of oncology trials. A computational visualization and analysis platform that can support novel analyses of combined clinical, genetic, imaging, biomarker data with other novel modalities will be critical to the success of these endeavors.